REVISITING FEMALE WORKERS’ THINKING ON PUBLIC SERVICE ADVERTISEMENT - Andayani, Wuwuh; Boeriswati, Endry; Anwar, Miftahulkhairah (Proceeding of International Seminar on Humanity, Education, and Language, 2026)
In the digital era characterized by an overwhelming and interconnected flow of information, individuals are increasingly required to possess critical skills in interpreting visual messages. However, the ongoing crisis in information literacy poses a significant challenge in understanding public messages conveyed through visual media. Public messages presented in the form of public service advertisements (PSAs) hold strategic potential when delivered with communicative and persuasive visual elements. This study revisits the perspectives of female workers toward PSAs to explore how they interpret such public messages. Employing a phenomenological-narrative approach, data were collected through in-depth interviews with female workers from diverse age groups and educational backgrounds. The data were analyzed using Atlas.ti software. The findings reveal that female workers actively engage in visual interpretation through three primary dimensions: active selection, visual symbolic structuring, and contextual emotional resonance. Informants tended to select familiar visual elements, interpret the design structure, and relate them to their lived experiences. This interpretive process reflects a form of critical visual literacy grounded in social and emotional realities. The theoretical contribution of this study lies in enriching the discourse on visual media literacy by foregrounding the often-marginalized voices of female workers in public communication design. Practically, the study highlights the necessity for inclusive and socially sensitive public communication strategies to more effectively engage audiences.